Adsorption Studies on the Removal of Anionic and Cationic Dyes from Aqueous Solutions Using Discarded Masks and Lignin - Penghui Li; Chi Yang; Yanting Wang; Wanting Su; Yumeng Wei; Wenjuan Wu (Molecules, 2023)
The carbon materials derived from discarded masks and lignin are used as adsorbent to remove two types of reactive dyes present in textile wastewater: anionic and cationic. This paper introduces the results of batch experiments where Congo red (CR) and Malachite green (MG) are removed from wastewater onto the carbon material. The relationship between adsorption time, initial concentration, temperature and pH value of reactive dyes was investigated by batch experiments. It is discovered that pH 5.0–7.0 leads to the maximum effectiveness of CR and MG removal. The equilibrium adsorption capacities of CR and MG are found to be 232.02 and 352.11 mg/g, respectively. The adsorption processes of CR and MG are consistent with the Freundlich and Langmuir adsorption models, respectively. The thermodynamic processing of the adsorption data reveals the exothermic properties of the adsorption of both dyes. The results show that the dye uptake processes follow secondary kinetics. The primary adsorption mechanisms of MG and CR dyes on sulfonated discarded masks and alkaline lignin (DMAL) include pore filling, electrostatic attraction, π-π interactions and the synergistic interactions between the sulphate and the dyes. The synthesized DMAL with high adsorption efficiency is promising as an effective recyclable adsorbent for adsorbing dyes, especially MG dyes, from wastewater.